2012
DOI: 10.3390/s120404065
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Quenching Bacillus sonorensis Isolated from Soya Sauce Fermentation Brine

Abstract: An N -acylhomoserine lactone (AHL)-degrading bacterial strain, L62, was isolated from a sample of fermentation brine of Chinese soya sauce by using rich medium agar supplemented with soya sauce (10% v/v). L62, a rod-shaped Gram positive bacterium with amylolytic activity, was phylogentically related to Bacillus sonorensis by 16S ribosomal DNA and rpoB sequence analyses. B. sonorensis L62 efficiently degraded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Recently, B. amyloliquefaciens , B. subtilis , B. mycoides and B. marcorestinctum were shown to have AHL-degrading activities, whereas AHL-degrading activity has not yet been reported for B. pseudomycoides [11,12,25,26]. AHL-degrading B. sonorensis L62 was isolated from a sample of the fermentation brine of Chinese soy sauce [27], which efficiently degraded N -(3-oxohexanoyl)- homoserine lactone (3-oxo-C6-HSL) and N -octanoyl-homoserine lactone (C8-HSL). The aiiA homologue was not detected in B. sonorensis L62, suggesting the presence of a different AHL-degrading gene in the strain L62.…”
Section: Biodiversity Of Organisms With Potential To Quench Qs Sigmentioning
confidence: 99%
“…Recently, B. amyloliquefaciens , B. subtilis , B. mycoides and B. marcorestinctum were shown to have AHL-degrading activities, whereas AHL-degrading activity has not yet been reported for B. pseudomycoides [11,12,25,26]. AHL-degrading B. sonorensis L62 was isolated from a sample of the fermentation brine of Chinese soy sauce [27], which efficiently degraded N -(3-oxohexanoyl)- homoserine lactone (3-oxo-C6-HSL) and N -octanoyl-homoserine lactone (C8-HSL). The aiiA homologue was not detected in B. sonorensis L62, suggesting the presence of a different AHL-degrading gene in the strain L62.…”
Section: Biodiversity Of Organisms With Potential To Quench Qs Sigmentioning
confidence: 99%
“…Anti-QS effects can be achieved by enzymatic approaches or using natural products [13]. Many quorum quenching bacteria producing AHL degradation enzymes have been isolated and studied [14–17]. Recent studies have demonstrated that QS antagonist compounds can be found in higher plants such as peas, vanilla, raspberry, Melicope lunu-ankenda , clove, and Myristica cinnamomea [1823].…”
Section: Introductionmentioning
confidence: 99%
“…When the concentration of these AHLs reaches the threshold level, the AHL-luxR complex will regulate a set of genes which occur in a population density-dependent manner, leading to population driven changes in several functions including virulence determinants, antibiotic production, bioluminescence, and biofilm formation [10–13]. QS bacteria have been isolated from various sources and habitats, including the human body [1418]. …”
Section: Introductionmentioning
confidence: 99%